Analisis Hubungan Pola Tidur dan Stres Akademik pada Mahasiswa - Zaky Setiawan; Richky Rahmadan; Muhammad Fathir Nur Alif Ekaputra; Sri Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
College represents a critical transitional period requiring high adaptation, where students often face escalating academic demands triggering psychological pressure. This study aims to deeply analyze the reciprocal relationship between sleep patterns and academic stress levels, and identify their subsequent impacts on cognitive function (concentration) and students' physical health. This study employs a qualitative method with a Systematic Literature Review approach. Data were collected through comprehensive searches of accredited national and reputable international scientific articles published within the last five years (2020–2025). Literature selection was conducted rigorously using specific keywords to screen empirical studies relevant to stress, sleep, and student health variables. Data synthesis reveals a strong and consistent negative correlation. High levels of academic stress whether stemming from the adaptation phase of new students (initiation), thesis preparation workload, or role conflicts in working students are significantly associated with decreased sleep quality. Physiologically, stress triggers increased cortisol levels causing insomnia, shortened sleep duration, and prolonged sleep latency. Subsequent impacts are proven to drastically reduce learning concentration and trigger physical health disorders, including an increased risk of primary dysmenorrhea in female students. This study concludes that academic stress and sleep disturbances form a destructive cycle that exacerbates one another. Therefore, holistic institutional interventions in the form of sleep hygiene education and stress management training are needed to break this chain for the sake of student well-being and academic performance.